Trimester two gestational exposure to bisphenol A and adherence to mediterranean diet are associated with adolescent offspring oxidative stress and metabolic syndrome risk in a sex-specific manner - Zamora, Astrid N.; Marchlewicz, Elizabeth; Téllez-Rojo, Martha M.; Burant, Charles F.; Cantoral, Alejandra; Song, Peter X. K.; Mercado, Adriana; Dolinoy, Dana C.; Peterson, Karen E. (Frontiers in Nutrition, 2022)
Background Exposure to prenatal bisphenol A (BPA) and Mediterranean Diet Score (MDS) has been linked to metabolic risk in child offspring. It remains unclear if independent and interactive effects persist in adolescence. Methods We examined prenatal BPA and MDS on adolescent offspring metabolic syndrome risk score (MRS) and 8-isoprostane (8-iso), a biomarker of oxidative stress. Data from maternal-adolescent dyads from a Mexico City cohort were utilized, including trimester-specific prenatal BPA from spot urine and MDS from food frequency questionnaires. Offspring socio-demographic data and biomarkers to estimate MRS and 8-iso were obtained during peri-adolescence. Results Adjusted linear regression models examined associations between trimester-specific BPA, MDS, and BPA*MDS on outcomes. Sex-stratified analyses revealed a significant association between MDS with increased 8-iso (β = 0.064, p < 0.05), and a marginal association between trimester two BPA with increased 8-iso (β = 0.237), while MDS modified the marginal association between BPA and 8-iso in females (β = 0.046). A negative, marginal association was observed between trimester two BPA and MRS (β = – 0.728), while BPA * MDS was marginally, positively associated with MRS (β = 0.152) in males. Conclusions Study findings indicate that trimester two prenatal BPA and maternal adherence to a Mediterranean diet may have sexually dimorphic effects on adolescent offspring oxidative stress and metabolic syndrome risk.